ANALYSIS OF INVESTMENT, FOREIGN INVESTMENT, WORKFORCE, AND EXCHANGE RATE INFLUENCE FOR ECONOMIC GROWTH IN NORTH SUMATERA - Yasmurni Zebua; Muhammad Fitri Rahmadana; Muhammad Nasir; Muammar Rinaldi (Advances in Social Sciences Research Journal, 2019)
The purpose of this study is to analyze the effect of the Foreign Investment, Domestic Investment , Workforce, and Exchange Rate on the economic growth of North Sumatra Province. This research is a study of how the factors that influence economic growth, which are the variables in this study are correlated. Moreover, after that, we can see which factors or variables have the most significant role in influencing economic growth in North Sumatra Province during the period 2001 to 2017. The type of data used in this study is secondary data in the form of time series data in the observation period 2001-2017, obtained from Bank Indonesia and the Central Bureau of Statistics. The analysis used is VAR; this model is used to explain the dynamic behavior between the variables observed and interrelationships. The results showed that the short-term Impulse Response Function test that most contributed to the workforce are domestic investment, followed by foreign investment, economic growth, and the exchange rate. For the medium term, the most significant contribution to the workforce are domestic investment, economic growth, foreign investment, and the exchange rate. In the long term, the most contributing to the workforce are domestic investment, foreign investment, economic growth, and the exchange rate. Based on the results of the Impulse Response Function test in the short term that most contribute to the exchange rate are the workforce, domestic investment, followed by foreign investment, and economic growth.